Branko Beslin’s Monograph about Eugene of Savoy – A Historical Panorama of an Epoch - Elezović, Dalibor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
Бешлин, Б. (2014). Евгеније Савојски и његово доба. Нови Сад: Матица српска.